Two Distinct Etiologies of Gastric Cancer: Infection and Autoimmunity - Hoft, Stella G.; Noto, Christine N.; DiPaolo, Richard J. (Frontiers in Cell and Developmental Biology, 2021)
Gastric cancer is a leading cause of mortality worldwide. The risk of developing gastric adenocarcinoma, which comprises >90% of gastric cancers, is multifactorial, but most associated with Helicobacter pylori infection. Autoimmune gastritis is a chronic autoinflammatory syndrome where self- reactive immune cells are activated by gastric epithelial cell autoantigens. This cause of gastritis is more so associated with the development of neuroendocrine tumors. However, in both autoimmune and infection-induced gastritis, high risk metaplastic lesions develop within the gastric mucosa. This warrants concern for carcinogenesis in both inflammatory settings. There are many similarities and differences in disease progression between these two etiologies of chronic gastritis. Both diseases have an increased risk of gastric adenocarcinoma development, but each have their own unique comorbidities. Autoimmune gastritis is a primary cause of pernicious anemia, whereas chronic infection typically causes gastrointestinal ulceration. Both immune responses are driven by T cells, primarily CD4+ T cells of the IFN- producing, Th1 phenotype. Neutrophilic infiltrates help clear H. pylori infection, but neutrophils are not necessarily recruited in the autoimmune setting. There have also been hypotheses that infection with H. pylori initiates autoimmune gastritis, but the literature is far from definitive with evidence of infection-independent autoimmune gastric disease. Gastric cancer incidence is increasing among young women in the United States, a population at higher risk of developing autoimmune disease, and H. pylori infection rates are falling. Therefore, a better understanding of these two chronic inflammatory diseases is needed to identify their roles in initiating gastric cancer.